The Role of LncRNA NEAT1 in Gastric Cancer: Tumor Development and Potential Therapeutic Target - Zhang, Yi; Wen, Yu (Current Pharmaceutical Design, 2023)
Background: The literature review reveals that NEAT1 is dysregulated in gastric cancer and plays a critical role in various aspects of tumorigenesis, including cell proliferation, invasion, metastasis, and chemotherapy resistance. NEAT1 exerts its functions through interactions with proteins, DNA, and other RNAs, acting as a scaffold or by modulating chromatin modifications and gene expression. Furthermore, NEAT1 is involved in epithelial-mesenchymal transition (EMT), angiogenesis, and immune evasion, contributing to the aggressive behavior of gastric cancer cells. The dysregulation of NEAT1 has been reported to be associated with clinicopathological features, prognosis, and therapeutic response in gastric cancer patients. Methods: A systematic literature search was performed on PubMed from September 2016 to the present using the keywords “LncRNA NEAT1” and “gastric cancer”. A total of 32 articles were identified. Studies investigating the regulatory mechanisms of NEAT1 in other tumors were excluded from this review. Additionally, to provide a more comprehensive understanding of the molecular mechanisms underlying NEAT1-mediated gastric cancer development, 27 additional articles were included. Results: LncRNA NEAT1 plays a pivotal role in gastric cancer, exerting significant effects on proliferation, invasion, metastasis, autophagy, apoptosis, drug resistance, and overall survival. The underlying molecular mechanisms involve miRNA sequestration, protein-protein interactions, transcriptional regulation, DNA methylation modifications, and activation of canonical signaling pathways. These findings underscore the multifaceted involvement of lncRNA NEAT1 in the pathogenesis and therapeutic resistance of gastric cancer, providing valuable insights into potential therapeutic targets and prognostic biomarkers. Conclusion: LncRNA NEAT1 is intricately involved in the pathogenesis of gastric cancer through various molecular mechanisms. Additionally, lncRNA NEAT1 is closely associated with radiotherapy resistance and adverse prognosis in gastric cancer patients, indicating its potential as a promising independent risk factor for clinical treatment targeting and prognostic prediction.
Keywords: epithelial-mesenchymal transition